2019
DOI: 10.1080/17461391.2019.1596165
|View full text |Cite
|
Sign up to set email alerts
|

Men vs. women world marathon records’ pacing strategies from 1998 to 2018

Abstract: The aim of this study was to analyse the pacing strategies adopted by elite male and female marathon runners when setting every world record since 1998. For data analysis, the total distance of the marathon was divided into eight sections of 5 km and a final section of 2.195 km, and the relative average speed of each section was calculated individually. Female athletes maintained similar speeds in the first and second half of the marathon (ES = 0.22, small effect, p = 0.705), whereas male athletes increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…This pacing strategy is characterised by a gradual decline of the athlete's speed throughout the race distance (Abbiss & Laursen, 2008). This is a common race strategy among male long-distance athletes in other sports like running (Díaz et al, 2019), and cycling (Abbiss & Laursen, 2008). Despite it cannot be found in the literature up-to-date information about elite 1500 m race stability, it was indicated that if swimmers could change their lap profile (reducing their lap variation) their performance could be improved (Lipinska et al, 2016b).…”
Section: Lap Performancementioning
confidence: 99%
“…This pacing strategy is characterised by a gradual decline of the athlete's speed throughout the race distance (Abbiss & Laursen, 2008). This is a common race strategy among male long-distance athletes in other sports like running (Díaz et al, 2019), and cycling (Abbiss & Laursen, 2008). Despite it cannot be found in the literature up-to-date information about elite 1500 m race stability, it was indicated that if swimmers could change their lap profile (reducing their lap variation) their performance could be improved (Lipinska et al, 2016b).…”
Section: Lap Performancementioning
confidence: 99%
“…In addition, it was notable in the marathon that men started slower than women, ran faster in the middle section, but then slowed more than women toward the finish (Figure 7). The pacing profiles in these championship marathons differed from those found in world record performances (Díaz et al, , 2019 where pacemakers help the best athletes achieve even or negative pacing and highlights the need for athletes and coaches to appreciate the differences between championship and non-championship racing.…”
Section: Discussionmentioning
confidence: 88%
“…One of the most important factors influencing marathon performance is the pacing adopted by athletes (Abbiss and Laursen, 2008;Díaz et al, , 2019. Athletes aim to efficiently use and distribute their energetic resources during athletic competition (Foster et al, 1994), with the aim of using all available reserves before reaching the finish, thereby avoiding premature fatigue (Skorski and Abbiss, 2017) and a significant deceleration before the end (Foster et al, 2004;Hettinga et al, 2007;Tucker and Noakes, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been established that the pacing strategy adopted has a major influence on the performances achieved by world record breaking athletes . In recent years, the world records have been achieved through progressively more consistent strategies than was the case in record performances of more than 25 years ago, which were typically characterized by a progressive reduction in speed (Díaz et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%